An interprovincial comparison of unintentional childhood injury rates in Canada for the period 2006–2012 - Fridman, Liraz (Can J Public Health, 2018)
OBJECTIVES: To perform an interprovincial comparison of unintentional population-based injury hospitalization and death rates for Canadian children ages 0–19 years and compare trends between 2006 and 2012. METHODS: Annual population-based hospitalization rates per 100,000 from unintentional injuries were calculated for children/youth (< 19 years) using data from the Discharge Abstract Database between 2006 and 2012. Annual mortality rates were analyzed using provincial coronial data. The mean annual change in the rate of hospitalizations due to unintentional injuries was reported for each province. RESULTS: The average annual rate of hospital admissions for unintentional injuries was 305.10 per 100,000 population between 2006 and 2012, and this decreased by − 11.91 over time (p < 0.01, − 15.85; − 7.77). Saskatchewan had the highest average annual morbidity rate (550.76 per 100,000) from all unintentional causes, and Ontario had the lowest average annual rate (238.89 per 100,000). Saskatchewan had the highest average annual rate for all subcauses except for drowning. Ontario was the only province with an average annual injury morbidity rate that was consistently below the Canadian average. The average annual mortality rate from all unintentional injury was highest in Saskatchewan (17.51 per 100,000) and lowest in Ontario (5.99 per 100,000) when compared to Canada (7.97 per 100,000). CONCLUSION: Injury prevention policies vary considerably among provinces. Although the unintentional injury hospitalization rate is decreasing over time, some subcauses such as choking/suffocation have shown an increase in certain provinces. Evidence-based childhood injury prevention policies, such as playground equipment safety and four-sided pool fencing among others, should be standardized across Canada.